2023
DOI: 10.3390/w15081617
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of the Use of the InVEST Annual Water Yield Model for the Rivers of Colombia: A Case Study of the Meta River Basin

Abstract: This paper presents the results of one of the hydrological models, the InVEST “Annual Water Yield” (InVEST–AWY), applied to the Meta River basin in Colombia, which covers an area of 113,981 km². The study evaluates the performance of the model in different subbasins of the Meta River basin. The model’s accuracy was assessed using different statistical measures, including Nash–Sutcliffe Efficiency (NSE) coefficient, Root Mean Square Error (RMSE), correlation coefficients for the calibration (rcal) and validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Several studies have carried out sensitivity analyses [3,58] on the model's results which allows them to be solid and reliable, comparing them to real values. Additionally, scenario analysis such as in the study carried out by [40] allows for the prediction of water yield behavior in future years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have carried out sensitivity analyses [3,58] on the model's results which allows them to be solid and reliable, comparing them to real values. Additionally, scenario analysis such as in the study carried out by [40] allows for the prediction of water yield behavior in future years.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology flow chart (Figure 2) was adapted from the study conducted by [3]. The same procedure was applied for both years, 1984 and 2022, with the inputs of the root boundary layer depth, the study area and the available water content for plants being constant parameters for both years when calculating water performance.…”
Section: Model Inputsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite limitations assessing model performance, several studies have shown that relatively simple models with limited data requirements can credibly simulate flows and water balance components in large, data-poor basins. Valencia et al [9] used the annual water yield model from the INVEST package to quantify current water yields in specific subbasins in the Meta River basin, Colombia. The study [10] also demonstrated the application of a distributed hydrological model like MIKE-SHE in data-scarce watersheds to assess climate change impacts on water resources, using limited meteorological and hydrological data for model input.…”
Section: Introductionmentioning
confidence: 99%